Impersonation dan Dark Jokes sebagai Tindakan Cyberbullying dalam Fenomena Bahasa “Anak Jaksel” di Media Sosial Twitter - Nadya Poernamasari (Journal of Social, Culture, and Language, 2023)
Language is a variety of spoken and non-spoken which becomes verbal and non-verbal language in the communication science. The presence of the “Anak Jaksel